The Central Role of Multiple P450 Genes and Their Co-factor CPR in the Development of Permethrin Resistance in the Mosquito Culex quinquefasciatus - Gong, Youhui; Li, Ting; Li, Qi; Liu, Shikai; Liu, Nannan (Frontiers in Physiology, 2022)
Mosquitoes’ increasing resistance to insecticides is becoming a major threat for control efforts worldwide. Multiple P450 genes that are up-regulated in permethrin resistant strains of Culex quinquefasciatus have been linked to the development of resistance. In the current study, we characterized the function of six P450 genes, CYP6P14, CYP6BZ2, CYP9J33, CYP9J34, CYP9J40 and CYP9J45, that are overexpressed in the permethrin resistant Culex mosquitoes and showed their capability in metabolism of permethrin. These six P450 genes can convert 3-phenoxybenzoic alcohol (PBCHO) to a less toxic product, 3-phenoxybenzoic acid (PBCOOH), indicating that these P450s play an important role in permethrin degradation pathways. Although we know multiple P450 genes are over-expressed in permethrin resistant Culex mosquitoes, it remains to be seen whether cytochrome P450-reductase (CPR) gene that are co-overexpressed with P450 genes in permethrin resistant mosquitoes do indeed serve as a resistance mechanism. An in-depth investigation of the expression of CPR gene in resistant mosquitoes was conducted in permethrin resistant mosquitoes. The finding of CPR gene overexpression in permethrin resistant mosquitoes suggested the importance of co-overexpression of multiple P450 genes with their obligatory electron donor CPR in the complex detoxification system, boosting the metabolism of permethrin and hence the development of permethrin resistance in Cx. quinquefasciatus.